2003
DOI: 10.1088/0268-1242/18/6/332
|View full text |Cite
|
Sign up to set email alerts
|

Novel optical devices based on surface wave excitation at conducting interfaces

Abstract: In this paper, the excitation of surface waves in the presence of interface charges is discussed. Interface charges affect the dispersion of surface waves, and therefore they can be used in various applications such as optical modulators, switches, sensors and filters. These waves can be superior to surface plasmon waves since they are not lossy. The lossless property is satisfied in a limited range of millimetre waves to far infrared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We report, in Fig. 3, the maximum of absorption for each n p case as a function of the angular (a) or spectral (b) illumination bandwidths, defined respectively by equations (8) and (15).…”
Section: From the Absorption Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…We report, in Fig. 3, the maximum of absorption for each n p case as a function of the angular (a) or spectral (b) illumination bandwidths, defined respectively by equations (8) and (15).…”
Section: From the Absorption Point Of Viewmentioning
confidence: 99%
“…Dielectric multi-layers have been widely investigated using either Bloch waves and band structures considerations [1][2][3][4][5][6][7][8][9][10] or optical thin film concept [11][12][13][14][15][16]. In both cases, very sharp resonances, spectrally and angularly, are anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…3 From the practical point of view, Tamm states could be implemented for the fabrication of polariton lasers 4 and optical modulators or filters. 5 In optics, these surface waves have been studied in both linear and nonlinear media. For a linear medium, Kossel has suggested that localized states could exist near the boundary between a homogeneous and a layered medium.…”
mentioning
confidence: 99%
“…More than a decade ago, we coined the term Conducting Interface to a family of optoelectronic devices, in which the electrooptic effect is maintained by a surface accumulation or depletion of electric charges [8][9][10][11][12][13][14]. While nowadays, graphene might be regarded as the ultimate conducting interface, our initial speculation [8] had been directed towards the inversion and depletion layers, surface states [11], and in particular, the quantum confined Two-Dimensional Electron Gas (2DEG) in III/V heterostructures.…”
Section: Index Terms-mentioning
confidence: 99%